Impact of Flow on Prosthesis-Patient Mismatch Following Transcatheter and Surgical Aortic Valve Replacement. (August 2021) - Abbas, Amr E.; Ternacle, Julien; Pibarot, Philippe; Xu, Ke; Alu, Maria; Rogers, Erin; Hahn, Rebecca T.; Leon, Martin; Thourani, Vinod H.
Abstract : Background: Severe prosthesis-patient mismatch (PPM) is diagnosed by an indexed effective orifice area <0.65 cm 2 /m 2, which is derived from stroke volume index. We examined the impact of flow, determined by stroke volume index, on severe PPM following transcatheter aortic valve replacement (TAVR) and surgical aortic valve replacement (SAVR). Methods: We included SAVR patients from the PARTNER 2A trial (Placement of Aortic Transcatheter Valve 2A) and TAVR patients from the PARTNER 2 S3i (Placement of Aortic Transcatheter Valve 2 S3i) registry. The primary end point was the separate analysis of all-cause death, cardiac death, and rehospitalization at 5 years. Following TAVR and SAVR, we compared the primary end points between severe versus no-severe PPM in all patients, in low flow (LF), and in normal flow. Multivariable analysis was performed to determine variables associated with the end points. Results: Nine hundred fifty-four TAVR and 726 SAVR patients with PPM and flow data were included. Severe PPM following TAVR was significantly lower compared with SAVR in all patients (9% versus 28%, P <0.0001), in normal flow (5% versus 8%, P =0.04), and in LF (20% versus 42%, P <0.0001). Severe PPM was associated with rehospitalization following TAVR (odds ratio, 1.52 [95% CI, 1.01–2.29], P =0.0456) and SAVR (odds ratio, 1.51 [95% CI, 1.06–2.16], P =0.0237). Severe PPM in LF was independently associated with cardiac death following TAVR (odds ratio, 1.85 [95% CI, 1.06–3.23], P =0.0308). Following SAVR, severe PPM in LF and low ejection fraction was associated with increased cardiac death (35.26% versus 12.51%, P =0.01) and rehospitalization (37.59% versus 15.46%, P =0.006) compared with severe PPM in LF and preserved ejection fraction, respectively. Severe PPM in normal flow was not associated with clinical outcomes despite higher gradients and smaller valves compared with severe PPM in LF. Conclusions: Severe PPM is more common following SAVR compared with TAVR. Regardless of the implanted valve size or gradient, severe PPM impacts mortality only in patients with LF following TAVR and LF and low ejection fraction following SAVR. Severe PPM in normal flow is not associated with poor outcomes. Registration: URL: https://www.clinicaltrials.gov ; Unique identifiers: NCT01314313 and NCT02687035. Abstract : Supplemental Digital Content is available in the text.